Friedman Redux : External Adjustment and Exchange Rate Flexibility - Ghosh, Atish (IMF Working Papers; Working Paper ;, 2014)
Milton Friedman argued that flexible exchange rates would facilitate external adjustment. Recent studies find surprisingly little robust evidence that they do. We argue that this is because they use composite (or aggregate) exchange rate regime classifications, which often mask very heterogeneous bilateral relationships between countries. Constructing a novel dataset of bilateral exchange rate regimes that differentiates by the degree of exchange rate flexibility, as well as by direct and indirect exchange rate relationships, for 181 countries over 1980-2011, we find a significant and empirically robust relationship between exchange rate flexibility and the speed of external adjustment. Our results are supported by several "natural experiments" of exogenous changes in bilateral exchange rate regimes.